The determinant factors for Quality of Life (QOL) among children with Acute Lymphoblastic Leukemia (ALL) after induction phase at Sanglah General Hospital, Bali, Indonesia - Made Suadnyani Pasek; Ketut Ariawati; Bagus Ngurah Putu Arhana; I Gusti Lanang Sidiartha; I Gusti Ngurah Sanjaya Putra; I Gusti Ngurah Made Suwarba (Intisari Sains Medis, 2020)
Background: The Quality of Life (QOL) of patients with acute lymphoblastic leukemia (ALL) is important to be examined. Some determinant factors of the QOL for ALL patients are age, gender, ethnicity, nutritional status, level of income of parents, educational level of parents, and risk groups. This study aims to determine the quality of life score among children with ALL after the induction phase of chemotherapy and to determine determinant factors that are associated with the quality of life of children with ALL.Methods: An observational analytic study using a cross-sectional approach has been conducted among 38 ALL patients to assess the QOL after the induction phase chemotherapy at Sanglah General Hospital. The independent sample T test evaluated comparative values between independent factors. Multivariate analysis was assessed by the General Linear Model ANCOVA. Data were analyzed using SPSS version 20 for Windows.Results: Most of the respondents were age > 5 years old (55.3%), followed by the male (55.3%), well-nourished of nutritional status (55.3%), low parentsâ€™ educational status (55.3%), a high income of parents (52.6%), standard risk of stratification (52.6%), and non-Balinese ethnicity (55.3%). The mean score of QOL was 79.37Â±21.64. The results showed that male gender (95% CI: 2.35-16.04; p=0.010), high income of parents (95% CI: 3.17-22.05; p=0.010), standard risk factors (95% CI: 1.48-16.36; p = 0.020) were significantly related to the QOL of children with ALL.Conclusion: High-income parents, standard risk stratification, and male gender are determinant factors for higher QOL scores of children with ALL after the chemotherapy induction phase.